2009
DOI: 10.1186/1479-5876-7-89
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells express CD25 and Foxp3 upon activation and exhibit effector/memory phenotypes without any regulatory/suppressor function

Abstract: BackgroundFoxp3 has been suggested to be a standard marker for murine Tregs whereas its role as marker for human Tregs is controversial. While some reports have shown that human Foxp3+ T cells had no regulatory function others have shown their role in the inhibition of T cell proliferation.MethodsT cell activation was performed by means of brayostatin-1/ionomycin (B/I), mixed lymphocyte reaction (MLR), and CD3/CD28 activation. T cell proliferation was performed using BrdU and CFSE staining. Flow cytometry was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 27 publications
4
113
1
2
Order By: Relevance
“…We used FOXP3 as an initial marker to identify early effectors, because the expression of this transcription factor is upregulated even on CD8 + T-cell activation (19)(20)(21). Expression of FOXP3 has been frequently reported to mark even CD8 + regulatory T lymphocytes found in cancer patients (28)(29)(30)(31)(38)(39)(40) The identification of the CD8 + subset described in this study as "early effectors" was corroborated by several lines of evidence.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We used FOXP3 as an initial marker to identify early effectors, because the expression of this transcription factor is upregulated even on CD8 + T-cell activation (19)(20)(21). Expression of FOXP3 has been frequently reported to mark even CD8 + regulatory T lymphocytes found in cancer patients (28)(29)(30)(31)(38)(39)(40) The identification of the CD8 + subset described in this study as "early effectors" was corroborated by several lines of evidence.…”
Section: Discussionmentioning
confidence: 69%
“…In fact, although FOXP3 marks subsets of CD4 + and CD8 + T lymphocytes with regulatory/ suppressive function (see refs. 17, 18, for review), it is also expressed by recently activated T cells that acquire effector functions (19)(20)(21). We found a CD8 + FOXP3 + T-cell subset enriched in TILN compared with TFLN and periphery and in advanced primary lesions compared with TILN.…”
Section: Cd127mentioning
confidence: 60%
“…Moreover, we also documented that suppressive T cells in cervical cancer patients had the CD4 + CD25 high Foxp3 + phenotype (23) and that, as in many malignancies, their presence impaired tumor immunity as reflected in worse patient survival (28). In contrast to the antigen-specific stimulation used here, strong mitogenic agents were reported to induce Foxp3 expression in nonsuppressive T cells (29,30). The tumor-specific immune response, the local environment, and immune escape mechanisms in HPV-induced cancers are similar to those in other immunogenic cancer types, and it is likely that the association of treatment failure and vaccine-enhanced Foxp3 + cells we describe can extend to immunotherapy with other tumor antigens.…”
Section: Discussionmentioning
confidence: 90%
“…It is probable that the expression of Foxp3 ocuurs in effector T cells as well as in Tregs. It has been reported that activated T cells can upregulate the expression of Foxp3 (48,49). There are several activated T cells, such as Th1, involved in PBMCs, which may indicate why the expression levels of Foxp3 are upregulated in PBMCs.…”
Section: Discussionmentioning
confidence: 99%